2010
DOI: 10.1111/j.1365-2591.2010.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic quality of root fillings performed by undergraduate students

Abstract: There is a need to improve the technical quality of root fillings performed by the undergraduate students, especially in molar teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
128
12
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(172 citation statements)
references
References 45 publications
21
128
12
11
Order By: Relevance
“…Similarly, conflicting findings were also reported by other studies from Europe and internationally (Balto et al 2010, Khabbaz et al 2010, Unal et al 2011, Elsayed et al 2011. Some of these variations may reflect differences in teaching and training but could also be due to the use of different methods and assessment criteria for radiograph evaluation.…”
Section: Accepted Articlementioning
confidence: 90%
“…Similarly, conflicting findings were also reported by other studies from Europe and internationally (Balto et al 2010, Khabbaz et al 2010, Unal et al 2011, Elsayed et al 2011. Some of these variations may reflect differences in teaching and training but could also be due to the use of different methods and assessment criteria for radiograph evaluation.…”
Section: Accepted Articlementioning
confidence: 90%
“…4,6,21,22,24,25 Certain studies have described a higher prevalence of apical periodontitis (60%-67.5%). 19,20 According to Khabbaz et al, 26 poorer dental health and inappropriate techniques may contribute to this higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by several epidemiological studies. 4,6,7,11,19,20,22,24,26,27,28,29,30,31 Ng et al 32 demonstrated the need to improve the technical quality of root fillings performed by undergraduate students, especially in molars. The technical quality of the root canal treatment and coronal restoration has a significant impact on the periapical health of root-filled teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several laboratory studies reported the advantages of using NiTi rotary instruments over manual preparation with hand files both for experienced and inexperienced operators (17)(18)(19), however, other studies (20) reported that even with the use of NiTi instruments, the technical quality of root fillings performed by students was "poor" and that tooth type significantly affected the quality of root fillings. Preparation of curved root canals in molar teeth by students has been associated with procedural errors (21), and curvature of canals has been found to be one of the main factors linked with poor quality root fillings performed by students and dentists (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%